Pentingnya Gizi Seimbang dalam Mencegah Stunting pada Anak Usia Dini - Regiska Falensya (Journal Innovation In Education, 2025)
Stunting is one of the chronic nutritional problems that continues to pose a major challenge in Indonesia and has a direct impact on the physical growth, cognitive development, and overall quality of life of young children. The golden period of child development, occurring between the ages of 0–5 years, is a critical stage that requires adequate balanced nutrition to ensure optimal growth and development. However, various national surveys such as SSGI show that the prevalence of stunting in Indonesia remains relatively high, reaching 21.6% in 2022 and decreasing to 19.8% in 2024, yet still far from the national target of 14%. This study aims to analyze the importance of implementing balanced nutrition as an effort to prevent stunting in early childhood and to explore the roles of parents, early childhood education institutions (PAUD), healthcare workers, and the community in supporting children's nutritional fulfillment. The method used is a literature review of government documents, recent journals, and nutrition guidelines such as DASHAT (2022). The findings indicate that balanced nutrition plays a significant role in preventing growth disorders because the proper fulfillment of macro and micronutrients supports cell formation, brain development, and immune function. The study concludes that stunting prevention requires cross-sector collaboration, comprehensive nutrition education, and the implementation of healthy eating habits from an early age to ensure children grow optimally and are protected from the risk of stunting.